Youth perception of the usage of wearable technology in technical MOOC education - Ahmad Fesol, Siti Feirusz; Arshad, Mohd Mursyid; Salam, Sazilah; Abu Samah, Khyrina Airin Fariza (Human Resource Management Academic Research Society, 2022)
Analysing youth learners' perception of the usage of wearable technology in technical education is reflected as the starting point towards a more effective and engaging learning environment. Previous research highlighted that one of the requirements for designing an engaging technical Massive Open Online Courses (MOOC) is to include a practice-oriented learning mode into its course structure. Therefore, this study aims to identify the learners' perception of the use of wearable technology in supporting the teaching and learning process specifically for technical course. This study adopted the case study methodology approach with quantitative analysis. The instruments used in this study include technical MOOC and wearable technology. A total of 375 engineering youth learners involved in this study and the data were analysed using descriptive and parametric testing. The survey results reflected that the learning materials produced by wearable technology do contribute towards positive perception in increasing the level of student's engagement with the learning process. Among key recommendations for future study are to implement the use of wearable technology for designing and developing other subjects as well